Pengaruh Motivasi Dan Stres Kerja Terhadap Kinerja Karyawan Divisi Telemarketing Dengan Budaya Organisasi Sebagai Variabel Intervening (Studi Pada Pt Sunlife Financial Indonesia - Nadia Ulfa; Tri Inda Fadhila Rahma; Nurbaiti Nurbaiti (STIE AMKOP, 2026)
This study aims to analyze the effect of work motivation and job stress on employee performance with organizational culture as an intervening variable in the telemarketing division of PT Sun Life Financial Indonesia. This study employs a quantitative approach using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) method. Data were collected through questionnaires distributed to all telemarketing employees.The results indicate that work motivation has a positive and significant effect on employee performance, while job stress has a negative and significant effect on employee performance. Organizational culture is also proven to have a positive effect on performance and is able to mediate the relationship between work motivation and job stress on employee performance. The R-square value of 0.63 indicates that the model explains 63% of the variance in employee performance.This study implies that improving employee performance can be achieved through strengthening work motivation, effectively managing job stress, and fostering a supportive organizational culture. Kata Kunci: Peran Pengawas Sekolah; Kompetensi Manajerial; Kepala Sekolah; Kinerja Guru.